(untitled) (Praxis Educativa, 2012)
How does the control process of school population occur? In this paper two complementary answers are presented: to change organization structures and to widen the organization processes. Regarding school structures, responsible people from the government take three kinds of decisions: to define standars of structural procedures at schools; to create good routines of school work and to build collective subjetivity in students. On the other hand, the strategy of organization processes and the education polices tend to promote inclusive cultures in each school center. Both political strategies of school behaviour control, try to identify each person and teacher with the institution. The consequence is exclusion of those who do not adapt to the requirements of school practices.